Stranded cetaceans warn of high perfluoroalkyl substance pollution in the western Mediterranean Sea. (December 2020) - López-Berenguer, G.; Bossi, R.; Eulaers, I.; Dietz, R.; Peñalver, J.; Schulz, R.; Zubrod, J.; Sonne, C.; Martínez-López, E.
Abstract: Perfluoroalkyl substances (PFASs) are a class of organohalogenated compounds of environmental concern due to similar characteristics as the well-studied legacy persistent organic pollutants (POPs) that typically show environmental persistence, biomagnification and toxicity. Nevertheless, PFAS are still poorly regulated internationally and in many aspects poorly understood. Here, we studied liver and muscle concentrations in five cetacean species stranded at the southeastern coast of Spain during 2009–2018. Twelve of the fifteen targeted compounds were detected in >50% of the liver samples. Hepatic concentrations were significantly higher than those in muscle reflecting the particular toxicokinetics of these compounds. Bottlenose dolphins Tursiops truncatus showed the highest hepatic ΣPFAS (n = 5; 796.8 ± 709.0 ng g −1 ww) concentrations, followed by striped dolphin Stenella coeruleoalba (n = 29; 259.5 ± 136.2 ng g −1 ww), sperm whale Physeter macrocephalus (n = 1; 252.8 ng g −1 ww), short-beaked common dolphin Delphinus delphis (n = 2; 240.3 ± 218.6 ng g −1 ww) and Risso's dolphin Grampus griseus (n = 1; 78.7 ng g −1 ww). These interspecies differences could be partially explained by habitat preferences, although they could generally not be related to trophic position or food chain proxied by stable N (δ 15 N) and C (δ 13 C) isotope values, respectively. PFAS profiles in all species showed a similar pattern of concentration prevalence in the order PFOS>PFOSA>PFNA≈PFFUnA>PFDA. The higher number of samples available for striped dolphin allowed for evaluating their PFAS burden and profile in relation to the stranding year, stable isotope values, and biological variables including sex and length. However, we could only find links between δ 15 N and PFAS burdens in muscle tissue, and between stranding year and PFAS profile composition. Despite reductions in the manufacturing industry, these compounds still appear in high concentrations compared to more than two decades ago in the Mediterranean Sea and PFOS remains the dominating compound. Graphical abstract: Image 1 Highlights: PFASs was measured in five endemic Mediterranean cetacean' species. PFAS burdens are higher than those reported two decades ago. PFOS and PFOSA are the dominant PFAS components of profiles. Concentrations were higher in the coastal bottlenose dolphin. Trophic position explains PFAS muscle burdens of striped dolphin. Abstract : Main findings: First study conducted in more than two decades of PFAS in stranded western Mediterranean. Despite its phase-out in the EU some of the PFAS burdens found can be considered high.